The question of effectiveness evaluation quality management system research organization - Лазько, Ирина Владимировна (Eastern-European Journal of Enterprise Technologies, 2011)
The Offered approach to estimation результативности managerial system by quality research organization, which is based on methodologies of the balanced system of the factors, and is organized his(its) practical approbation